KARAKTERISTIK KOMITE AUDIT, UKURAN PERUSAHAAN, DAN PROFITABILITAS TERHADAP TIMELINESS PELAPORAN KEUANGAN - Rahayu, Ruci Arizanda; Chosah, Zalzabela Aagata Widya; Maryanti, Eny (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
This study aims to examine the effect of audit committee’s characteristics consist of gender audit committee, meeting frequencies, work experience, firm size, and profitability on the timeliness of corporate financial reporting (Study of Multi-Industry Sector Manufacturing Companies Listed on the IDX in 2018-2021). The research method used is a descriptive quantitative approach. Then the type of data used is secondary data from financial reports on manufacturing companies in various industrial sectors listed on the IDX in 2018-2020. The sampling technique used in this study was using a purposive sampling method and obtaining a sample of 120 financial statements of manufacturing companies in various industrial sectors. The data analysis method in this research is assisted by the SPSS (Statistical Package for the Social Science) application. The results of tests conducted using SPSS revealed that the Gender of the Audit Committee, Company Size, Auditor's Work Experience at KAP did not affect the Timeliness of Financial Reporting. While Profitability and Frequency of Audit Committee Meetings affect the Timeliness of Financial Reporting.